EXPERIMENTAL METHODS AND PROSPEROUS MEDIA IN ELEMENTARY SCHOOL SCIENCE TO IMPROVE LEARNING OUTCOMES - Hartika Ayu Wardani (MEDIA DAN STRATEGI PEMBELAJARAN, 2024)
Science learning outcomes in material on the properties of sound in class IV elementary school are low, which is marked by a score below the KKM. To improve learning outcomes, teachers need to make efforts to use teaching aids as media. This research uses a PTK approach which goes through 4 stages, including planning, and implementation. observation and reflection. The research was carried out through 2 cycles where the results of the research showed that the average score for students in the first cycle was an average class score of 60.5 and 7 students who reached the KKM out of 20 students were categorized as still, it could not be said to have met the minimum completeness criteria, this was because Due to non-optimal learning activities, only 30% were completed, so it was necessary to carry out learning in cycle II. The final results showed that in cycle II with an average class score of 80.5 or 17 students had reached the KKM. Of the 20 students, they were categorized as reaching 85 % completed. Therefore, it can be concluded that there has been an increase in science learning outcomes at UPTD SDN 016547 Teluk Dalam, Teluk Dalam District, Asahan Regency for the 2023/2024 academic year using the experimental method using teaching aids. Experimental Methods, Learning Outcomes, Science Subjects.